“PENGARUH FRAUD HEXAGON, FAKTOR ORGANISASI DAN INTEGRITAS TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI” - Selviana Selviana; Irwansyah Irwansyah (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of the Fraud Hexagon, Organizational Factors and Integrity on the Academic Fraud Behavior of Bengkulu University Accounting Students. In this study, the population used was 165 people with the criteria being students of the 7th semester accounting study program who had taken audit courses and using a non-probability sampling method based on the results of calculations using the Slovin formula, a research sample of 117 students was obtained. In this research, the method used is a quantitative method in testing hypotheses and processing data using statistical data tools, namely SmartPLS 3.00. The results of this research show that the cheating hexagon factors that influence accounting students' academic cheating behavior are pressure, opportunity, ability and arrogance, while rationalization and collusion have no effect on accounting students' academic cheating behavior. Based on the research results, it was also found that organizational factors did not have a significant influence, while integrity had a negative influence on accounting students' academic fraudulent behavior.